Assessing The Physical And Psychological Well-Being Of Palestinian Medical Students Arriving At Rawalpindi Medical University - Riaz, Mehwish; Shahid, Rizwana; Asif, Omaima; Umar, Muhammad; Qureshi, Mahjabeen; Amjad, Tahira (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the physical and psychological well-being of Palestinian medical students carried out at Rawalpindi Medical University. Methods: A cross-sectional descriptive survey was carried out to analyse the physical and psychological health of Palestinian medical students who arrived at Rawalpindi Medical University in a desperate scenario. Apart from measuring vitals, Ophthalmic and ENT examinations of medical students were also done. Their comorbidities were also inquired, and influenza and typhoid vaccines were administered. Depression among students was categorised by using the Patient Health Questionnaire (PHQ-9) scale. Data was analysed by using Microsoft Excel 2016 software. Descriptive statistics were applied. Results: Of the 36 Palestinian medical students reaching RMU for continuation of medical education, 19 were males. The mean age of the students was 22.4 ± 1.45 years. Around 29 students were subjected to a physical and psychological health assessment. They were physically fit and healthy. 11 students were mildly depressed, and female students were comparatively more depressed than males. Conclusion: The medical students of Gaza were physically fit but depressed due to the disaster in their homeland